Development of Teacher Academic Optimism Scale: The Validity and Reliability Study - Ergen, Yusuf; Elma, Cevat (Pegem Akad Yayincilik Egitim Danismanlik Hizmetleri Tic Ltd Sti, 2018)
The study aims to develop a valid and reliable academic optimism scale that can be used to determine teachers' academic optimism levels. The study was conducted through a total number of 404 primary school teachers who worked in the central districts of Malatya Province during 2014-2015 academic year. The content validity and face validity of the scale were determined via expert recommendations. An explanatory factor analysis and a confirmatory factor analysis were conducted to determine the construct validity of the scale. After the expert opinions, 80 items reduced to 64 and the data was collected by the use of these 64 items. An exploratory factor analysis revealed 5 factors reducing 64 items in to 33 and explaining 58.56% of the total variation in the data. The five-factor model obtained through an explanatory factor analysis after removal of one item as a result of the confirmatory factor analysis was observed to be highly consistent. Different from previous related research, the result showed that a new dimension as "Maneger Trust" emerged as a part of "Teacher Academic Optimism Scale". And finally this scale could be used as a valid and reliable instrument in the future studies.
Keywords: Academic Optimism; Scale Development; Teacher